Modelling of ammonia absorption process: falling film and packed column - Santa Rosa, Licianne Pimentel (2021)
Absorbers belong to the group of industrial equipment used for separation/ purification of process streams. Among the equipment to promote the absorption, falling film and packed column have an extensively application in industrial plants. So, this thesis aims to propose a phenomenological model for a falling film absorber and to carry out a comparative study between it and a packed column. The falling film model is described by differential mass and energy balances coupled with algebraic equations representing the mass and energy transfer as well as the phase-equilibrium. This modeling approach based on a full DAE (Differential and Algebraic Equations) set is more robust and flexible than the usual approach reported in the literature, wherein sequential algorithms are specifically tailored to solve them model. A packed absorption column is designed by empirical correlations and simulated in Aspen Plus. This thesis also investigates the rigorous thermodynamic description of two possible working fluids: NH3-H2O and the electrolyte system NH3-H2O-CO2. The absorbers and thermodynamics models results are in accordance with the experimental data from literature. Regarding the comparative study of the absorbers, the technical analysis is based on phenomenological models to predict the efficiency of absorption, monitoring the temperature and concentration profiles. The economic analysis of the absorbers is based on the estimation of the investment and installation cost. The comparative study between the absorbers shows that the falling film type absorber has greater absorption capacity and it is 33% more compact than the column, although at the expense of doubling the investment. For higher concentration, the results suggest that the falling film absorber is preferable than the packed column.